A Macron Signifying Nothing: Revisiting the Canterbury Tales Project Transcription Guidelines. Issue 1 (9th November 2021) - Bitner, Kendall; Dase, Kyle
Abstract : The original transcription guidelines of The Canterbury Tales Project (CTP) were first developed by Peter Robinson and Elizabeth Solopova and were published in 1993. Since then, the project has evolved, bringing about numerous changes of varying degrees to the process of transcription. In this article, we revisit those original guidelines and the principles and aims that informed them and offer a rationale for changes in our transcription practice. We build upon Robinson and Solopova's assertion that transcription is a fundamentally interpretive act of translation from one semiotic system to another and explore the implications and biases of our own position (e.g. how our interest in the text of The Canterbury Tales prioritizes the minutiae of that text over certain features of the document). We reevaluate the original transcription guidelines in relation to the changes in the project's practices as a means of clarifying its position. Changes in the project's practice illustrate how it has adapted to accommodate both necessary compromises and more efficient practices that better reflect the original principles and aims first laid down by Robinson and Solopova. This article provides practical examples that demonstrate those same principles in action as part of the transcription guidelines followed by transcribers working on The Canterbury Tales Project. Rather than perceiving this project as producing a definitive transcription of the Canterbury Tales, the CTP team conceptualizes its work as an open access resource that will aid others in producing their own editions as it has done the heavy lifting of providing a base text.